A research on the allocation of rights and responsibilities in the three-dimensional marine blue carbon ecosystem under the background of marine carbon neutrality - Wang, Xiaoxu; Cao, Cheng (Frontiers in Marine Science, 2025)
Under the tide of global climate change, achieving carbon neutrality has become a common goal for the international community. The ocean, with its huge carbon storage capacity, has become a key link in the Earth’s carbon cycle. The ocean stores approximately 93% of the Earth’s total carbon dioxide and can remove over 30% of the atmospheric carbon dioxide each year. As the core force of marine carbon sink, blue carbon ecosystem through the high carbon sequestration efficiency of ecosystems such as mangroves, seagrass beds, and coastal salt marshes, plays an irreplaceable role in the global carbon cycle and climate regulation. Meanwhile, although the three-dimensional sea use model has effectively alleviated the industrial sea use contradiction caused by the scarcity of maritime spatial resources, it has also brought the threat of direct damage and indirect functional weakening to the blue carbon ecosystem. At present, there are legal gaps in relevant laws in China. In-depth research on their legal issues is of great significance for protecting the blue carbon ecosystem, promoting marine carbon neutrality and sustainable economic development.